VALUE-ADDED TAX REVENUE AND ECONOMIC GROWTH PARADOX IN NIGERIA (World Bulletin of Management and Law, 2024)
The necessity of economic growth paradox is a conventional wisdom of our time, assumed to lead to more prosperity and be a panacea for any social problem. However, infinite growth is hard to reconcile with a finite planet, and there is a growing body of evidence that suggests that growth is no panacea nor inherently linked to prosperity. The aim of this study is empirically explore the relationship between value added tax nexus and economic growth in Nigeria. the study adopted longitudinal research design and data were collected from central bank of Nigeria statistical bulletin, National Bureau of statistics, federal inland revenue statistic, annual report of central bank of Nigeria from 1994-2021 and the collected were analyzed using descriptive statistics, ordinary least square regression analysis, unit root test, co-integration test and error correction model with the aid of e-view version II. The results indicate that input tax positive and significantly relate to gross domestic product. In the same vein, output tax positively relates to gross domestic product. The study therefore concludes that the exist a strong relationship between value-added tax revenue and economic growth in Nigeria and recommends that the mono-product economy of Nigeria should be diversified along the line of taxation since there exist a positive relationship between taxation and economic growth in Nigeria. In addition, the drift from direct to indirect form of taxation as entrenched in the New National policy should be deemphasized as there exists a negative and insignificant relationship between value-added tax revenue and economic growth in Nigeria